Human Dignity and a Fair Trial - Celińska-Grzegorczyk, Katarzyna (Acta Universitatis Lodziensis. Folia Iuridica, 2023)
Human dignity has to be protected by all authorities. Dignity is a basis and source for all human rights, including right to a fair trial. The analysis of the relationship between human dignity and a right to a fair trial in polish administrative proceedings and proceedings before administrative courts is a subject of this article.